2020
DOI: 10.1097/01.ogx.0000669280.20035.ca
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Fraction and Noninvasive Prenatal Testing: What Clinicians Need to Know

Abstract: The fetal fraction (FF) is a function of both biological factors and bioinformatics algorithms used to interpret DNA sequencing results. It is an essential quality control component of noninvasive prenatal testing (NIPT) results. Clinicians need to understand the biological influences on FF to be able to provide optimal post-test counseling and clinical management. There are many different technologies available for the measurement of FF. Clinicians do not need to know the details behind the bioinformatics alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 69 publications
1
31
1
2
Order By: Relevance
“…In their recent review, Hui and Bianchi suggested that clinicians do not need to know the details behind the biological and technological reasons for cfDNA test failure, but they do need to have a "plan B" prepared for affected patients in their clinical practice. 27 Although waiting before redrawing a fresh sample will increase the probability of obtaining a result, the clinical utility of doing so must be considered. Redraws only resolve some of the cases and significantly increase turnaround time.…”
Section: Discussionmentioning
confidence: 99%
“…In their recent review, Hui and Bianchi suggested that clinicians do not need to know the details behind the biological and technological reasons for cfDNA test failure, but they do need to have a "plan B" prepared for affected patients in their clinical practice. 27 Although waiting before redrawing a fresh sample will increase the probability of obtaining a result, the clinical utility of doing so must be considered. Redraws only resolve some of the cases and significantly increase turnaround time.…”
Section: Discussionmentioning
confidence: 99%
“…9 Obese pregnant women are at higher risk of test failure due to LFF, probably due to dilution because of an increased circulating volume or by higher release of maternal cfDNA into the systemic circulation through apoptosis of adipose cells. 6,10,11 Other maternal factors such as ethnicity and smoking have too been found to influence fetal fraction. 6,12 Fetal aneuploidy has also been associated with LFF.…”
Section: Introductionmentioning
confidence: 99%
“…The 'fetal fraction' (FF) is the proportion of total maternal plasma cfDNA that arises from the fetoplacental unit, that is FF = cffDNA/(cffDNA + maternal plasma cfDNA). The FF is an important quality control metric in NIPT and is routinely calculated by most laboratories during the clinical workflow (Hui and Bianchi 2020). Nomenclature for cfDNA in prenatal testing is summarized in Fig.…”
Section: Prenatal Testingmentioning
confidence: 99%